1972
DOI: 10.1039/c39720000405
|View full text |Cite
|
Sign up to set email alerts
|

Oruwal, a novel dihydroanthraquinone pigment from Morinda lucida Benth.

Abstract: Sz.wzmary Four known anthraquinones, and a new compound oruwal which was characterized as 9,lO-dimethoxyanthracene-2-carbaldehyde from spectroscopic evidence and chemical transformation were isolated from Morinda lucida Benth. (Rubiaceae) ; oruwal is a possible intermediate in the biosynthetic route to some anthraquinones. Morinda lucidaBenth., known in the Western State of Nigeria as Oruwo, is a valuable tree used as a dye, and ir, native medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…9 Phytochemical researchers found that M. lucida is a natural resource rich in anthraquinones like oruwal, 3-hydroxyanthraquinone-2-carboxyaldehyde, 1,3-dihydroxy-2-methylanthraquinone, 1,3-dihydroxyanthraquinone-2-carboxyaldehyde and so on. [10][11][12][13] It is used among traditional healers to treat fever, dysentery, abdominal colic and intestinal worm infestation. Several groups have reported on its anti-protozoa activities and some active compounds isolated from M. lucida.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Phytochemical researchers found that M. lucida is a natural resource rich in anthraquinones like oruwal, 3-hydroxyanthraquinone-2-carboxyaldehyde, 1,3-dihydroxy-2-methylanthraquinone, 1,3-dihydroxyanthraquinone-2-carboxyaldehyde and so on. [10][11][12][13] It is used among traditional healers to treat fever, dysentery, abdominal colic and intestinal worm infestation. Several groups have reported on its anti-protozoa activities and some active compounds isolated from M. lucida.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have isolated one novel tetracyclic iridoid, named as molucidin, from the CHCl 3 fraction of the M. lucida leaves by bioassay-guided fractionation and purification. Molucidin was structurally elucidated by 1 H and 13 C NMR including HMQC, HMBC, H-H COSY and NOESY resulting in tetracyclic iridoid skeleton, and its absolute configuration was determined. We have further demonstrated that molucidin presented a strong anti-trypanosomal activity, indicating an IC 50 value of 1.27 lM.…”
Section: Introductionmentioning
confidence: 99%
“…3 Researchers found that M. lucida is a natural resource rich in antraquinones similar to oruwal, 3hydroxyanthraquinone-2-carboxyaldehyde, 1,3-dihydroxy-2methylanthraquinone, 1,3-dihydroxyanthraquinone-2carboxyaldehyde, and so on. [4][5][6][7] Furthermore, various iridoids have been isolated from Morinda spp. and other members from the Rubiaceae family.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] The plant contains anthraquinones, [16][17][18] iridoids, [19] triterpenoids [20] and volatile oil. [21] Extracts from M. lucida have shown some biological activities, comprising antimalarial, [17,20,[22][23][24][25] trypanocidal, [23] purgative, [26] anti-inflammatory and analgesic [27] and antimicrobial [18,28,29] activities. Meanwhile, the leaf and root extracts exhibit anti-diabetic activities [30,31] .…”
Section: Blood Glucose Measurementsmentioning
confidence: 99%